Language maintenance through corpus planning – the case of Kven. - Keränen, Mari (Acta Borealia, 2018)
This is an Accepted Manuscript of an article published by Taylor & Francis in Acta Borealia on 30. October 2018, available online: http://www.tandfonline.com/10.1080/08003831.2018.1536187 The Kven language that is spoken in northernmost Norway was officially recognized as a language in 2005. The history of the language community dates back to the sixteenth century according to tax books. There is still an ongoing discussion among certain language users, whether Kven is in fact a language or one of the Finnish dialects. The language planning of Kven has started in 2007 by determining the orthography and choosing principles for the standardization. This article discusses the history of the process that led to the recognition of Kven as a language and reviews the progress of the language standardization until the present. The principles of language planning are reviewed through document analysis – earlier literature, minutes or summaries and participant observation of the language board’s meetings, and expert interviews – and analysed according to Lars S. Vikør’s language planning model. Some of the preferred features seem to follow the language planning ideology of the Norwegian standards – Bokmål and Nynorsk – in terms of allowance of variation and parallel forms as well as dialectal diversity.